Numerical study of effects of stand-off distance and gravity on large scale bubbles near a breach. (December 2021) - He, Ming; Wang, Shi-Ping; Ren, Shao-Fei; Zhang, Shuai
Abstract: When a ship is subjected to a near-field underwater explosion, the strong shock waves may cause local damage or a breach in the ship's structure. The large-scale bubbles that subsequently form will expand and collapse according to the effects of the nearby breach. In the present paper, a bubble numerical setup for the region near a breach is established based on the Eulerian finite element method. This numerical setup is first verified through bubble experiments in a vacuum water tank that produces a strong buoyancy effect. The mechanism of coupling between the large-scale bubble and the breach is then studied under different standoff distances and gravitational effects. It can be concluded that the standoff distance determines the inrush pattern, with the various patterns including inrush with a bursting bubble, inrush with a gourd-shaped bubble, and inrush with a floating bubble. The volume and initial velocity of the inrush water varies with the standoff distance. Finally, the influence of gravity on the inrush process is analyzed. The initial stage of inrush is almost independent of gravity, although this soon gives way to a stage in which gravity has an obvious influence. As the bubbles float up and drive the surrounding water, the volume of inrush water suddenly increases under the effect of gravity. This paper aims to provide references for ship protection under UNDEX load. Highlights: The bubble pulsating model near a breach is established based on the EFEM. Different patterns of inrush are formed due to different standoff distances. The coupling mechanism is studied under different standoff distances and gravity effect.